2018
DOI: 10.1371/journal.pone.0209597
|View full text |Cite
|
Sign up to set email alerts
|

Different grain-filling rates explain grain-weight differences along the wheat ear

Abstract: Thousand grain weight is one of the components determining wheat grain yield. It represents the average value of individual grain weights which depends on position within the ear and on positon within the spikelet. Our objective was to quantify the influences of individual floret anthesis date, of carpel weight at anthesis and of rate and duration of grain filling, on variation in individual final grain weight. Two bread wheat cultivars were grown in a greenhouse and their ears were sampled from anthesis throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 34 publications
(82 reference statements)
1
29
1
Order By: Relevance
“…Other researchers such as Nass and Reiser (1975) and Borrill et al (2015) argue that the rate of grain filling or grain filling capacity is more critical than the grain filling duration. Madani et al (2010) and Baillot et al (2018) showed that the rate of translocation of photosynthates to the grain contributes to grain weight and is a major component of grain yield in wheat, which supports the statement that grain filling rate is more fundamental to grain yield than grain filling duration. There is also an argument that stressed plants may have a higher rate of grain filling, and this, combined with a shorter grain filling period, cause improper assimilate translocation which ultimately leads to reduced grain yield (Ihsan et al, 2016;Alghabari and Ihsan, 2018).…”
Section: Grain Filling Rate and Durationsupporting
confidence: 63%
“…Other researchers such as Nass and Reiser (1975) and Borrill et al (2015) argue that the rate of grain filling or grain filling capacity is more critical than the grain filling duration. Madani et al (2010) and Baillot et al (2018) showed that the rate of translocation of photosynthates to the grain contributes to grain weight and is a major component of grain yield in wheat, which supports the statement that grain filling rate is more fundamental to grain yield than grain filling duration. There is also an argument that stressed plants may have a higher rate of grain filling, and this, combined with a shorter grain filling period, cause improper assimilate translocation which ultimately leads to reduced grain yield (Ihsan et al, 2016;Alghabari and Ihsan, 2018).…”
Section: Grain Filling Rate and Durationsupporting
confidence: 63%
“…Values obtained for TGW and grain density were low compared with field trials, which have been reported above 40 g for TGW (Popko et al, 2018) and above 75 kg hl −1 in terms of density (Manley et al, 2009). However, Baillot et al (2018) showed a reduction in the TGW between field and greenhouse conditions. These trends are in accordance with our values (27-33 g).…”
Section: Discussioncontrasting
confidence: 58%
“…Indeed, an increase in GPS created a larger proportion of small grains [45], mainly through an increase of the number of grains in the distal positions of each spikelet [46]. These distal grains have been shown to be significantly smaller than the grains in proximal positions [47,46,48,49]. In addition, an increase in SPM2 implies a higher diversity in the spike population at the plot scale, with a larger proportion of spikes from secondary tillers [50].…”
Section: Gsv Is Partly Driven By Canopy Structurementioning
confidence: 99%